Genetic structure of the population of Suri alpaca from Peru - Gallegos Acero, Roberto (2023)
The objective of the study was to evaluate the genetic structure of the Suri alpaca population, from the Quimsachata Research and Production Center of the Illpa-Puno Experimental Station of the National Institute of Agrarian Innovation, Peru. Data from 1350 Suri alpacas born from 1993 to 2015 (636 males and 714 females) were analyzed using the method of genealogical analysis method. ENDOG program v.4.8 was used for the calculation of the following parameters of the genetic structure such as: average inbreeding coefficient (F), average relatedness coefficient (AR), the effective numbers of founders (ƒe), effective number of ancestors (ƒa), generation interval (GI) and the pedigree completeness, the ENDOG program v.4.8 was used. The F and AR were 0.06% and 0.40%, respectively, the number of ancestors that gave rise to the reference population was 288, the ƒa for the reference population was 132. The ƒe was 338 animals. The average generational interval was 5.53 years, being higher in the gametic pathways: sire-daughter and sire-son. The pedigree completeness level by the maternal pathway was 72.07% and by the paternal pathway was 46.0%. In conclusion, the generational interval in Suri alpacas of the Germplasm Center was long. The F was of small magnitude, so mating practices were appropriate during the evaluation period.